1993
DOI: 10.1016/0014-5793(93)81468-f
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐penetrating inhibitors of calpain block both membrane fusion and filamin cleavage in chick embryonic myoblasts

Abstract: Benzyloxycarbonyl(Z)-Leu-nLeu-H(calpeptin) and Z-Leu-Met-H, cell-penetrating mhtbitors of calpain. were found to block myoblast fusion without any effect on cell proliferation and alignment along then bipolar axts. They also inhibited the accumulation of creatine kinase during myogenesis. These effects were dose-dependent, and could be reversed upon removal of the drug from the culture medium. Furthermore, treatment of the inhibitors prevented the hydrolysis of filamm, which is sensitive to cleavage by calpam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…Filamin repeats near hinge-1 have been identified previously as the sites of interaction for androgen (28) and dopamine D 2 (29) receptors and tumor necrosis factor receptor-associated factor 2 (30), indicating a general role for this region in anchoring membrane-associated signaling proteins to the actin cytoskeleton. The hinge-1 region is also recognized for its susceptibility to cleavage by calcium-activated proteases such as calpain, which prevents filamin from cross-linking actin and alters the stability of the cytoskeletal network (31)(32)(33). Nephrocystin binding could alter the conformation of the hinge-1 region and affect cleavage, though we have been unable to show an effect of nephrocystin binding on filamin degradation by calpain in vitro.…”
Section: Discussionmentioning
confidence: 93%
“…Filamin repeats near hinge-1 have been identified previously as the sites of interaction for androgen (28) and dopamine D 2 (29) receptors and tumor necrosis factor receptor-associated factor 2 (30), indicating a general role for this region in anchoring membrane-associated signaling proteins to the actin cytoskeleton. The hinge-1 region is also recognized for its susceptibility to cleavage by calcium-activated proteases such as calpain, which prevents filamin from cross-linking actin and alters the stability of the cytoskeletal network (31)(32)(33). Nephrocystin binding could alter the conformation of the hinge-1 region and affect cleavage, though we have been unable to show an effect of nephrocystin binding on filamin degradation by calpain in vitro.…”
Section: Discussionmentioning
confidence: 93%
“…(ii) Inhibitors of protease activity some of which are specific for calpain (e.g., calpain antibody, human calpastatin peptide, endogenous rabbit calpastatin) inhibit seal formation in crayfish MGAs. (iii) Calpain is an endogenous protease in squid GAs (5), other axons (including the crayfish MGA) (4,6,8,10,20), and many other cell types (14)(15)(16)(17)(18)(19). (While other proteases may induce sealing in Ca 2ϩ -free salines in crayfish MGAs (this report) and in mammalian axons (11), these proteases are not known to be endogenous to these axons.)…”
Section: Resultsmentioning
confidence: 99%
“…Exogenously added calpain II was found to promote myoblast fusion (40). Studies using calpain inhibitors also showed that inhibition of the endogenous calpain can suppress myogenesis (14,41). Although possible roles of calpain II in muscle growth and differentiation have been postulated (6,42), the biochemical mechanism underlying its myogenic function is still unclear.…”
Section: Discussionmentioning
confidence: 99%